Bilateral Peritonsillar Abscesses: A Case Presentation and Review of the Current Literature with regard to the Controversies in Diagnosis and Treatment - G. X. Papacharalampous; P. V. Vlastarakos; G. Kotsis; D. Davilis; L. Manolopoulos (Case Reports in Medicine)
Although unilateral peritonsillar abscess is a common complication of acute bacterial tonsillitis, bilateral peritonsillar abscesses are quite rare. The incidence of unsuspected contralateral peritonsillar abscess identified at tonsillectomy has been reported to be between 1.9% and 24%, while the overall incidence of bilateral peritonsillar abscess is reported to reach 4.9%. Diagnosis can be based on clinical criteria or imaging techniques. As far as the treatment is concerned, it is generally accepted that the basic strategy consists of systemic antibiotics and drainage of the pus. We report the case of a 19-year-old girl, treated in the emergency room with a bilateral diagnostic needle aspiration followed by bilateral incision and drainage along with intravenous clindamycin plus anti-inflammatory agents and hydration. Following treatment, the patient progressively experienced a marked alleviation of her odynophagia. She was discharged 48 hours later on a 10-day course of clindamycin.